Breast abscess due to Salmonella enterica serovar Typhi in a young diabetic female (Ibrahim Medical College Journal, 2014)
Salmonella enterica serovar Typhi (S. Typhi) is occasionally associated with abscess formation in various organs of the body. But breast abscess by S. Typhi without the general and specific symptoms of typhoid fever is unusual. We report a case of breast abscess due to S. Typhi in a 20 year old nonlactating diabetic female without the features of typhoid fever. DOI: http://dx.doi.org/10.3329/imcj.v7i1.17743 Ibrahim Med. Coll. J. 2013; 7(1): 16-17